Methoxatin as a Target in Total Synthesis - Schröder, Birte; Gaich, Tanja (Synthesis, 2017)
Methoxatin is a redox co-factor with a unique structure featuring a central 1,2-benzoquinone, annulated to an electron-poor pyridine and an electron-poor pyrrole ring. This exceptional molecular structure leads to the unusual biological function of methoxatin, which therefore plays a significant role in metabolism. Hence, many total syntheses providing access to this remarkable natural product were published soon after the structure was elucidated.1 Introduction2 Structural Analysis3 Biological Function3.1 Biochemical Role3.2 Biosynthesis3.3 Biochemical Mechanism4 Completed Total Syntheses4.1 Hendrickson Group (A + C → C)4.2 Büchi Group (BC → ABC)4.3 Boger Group (BC → ABC)4.4 Weinreb Group (BC → ABC)4.5 Rees Group (BC → ABC)4.6 Corey and Martin Group (BC → ABC)5 Conclusion
Keywords: redox co-factors; biochemical function; biosynthesis; natural products; total syntheses